Porphyra yezoensis Sauces Fermented With Lactic Acid Bacteria: Fermentation Properties, Flavor Profile, and Evaluation of Antioxidant Capacity in vitro - Jie Yang; Jie Yang; Jie Yang; Tengqi Gao; Feng Ge; Hao Sun; Zihang Cui; Zhen Wei; Zhen Wei; Shujun Wang; Shujun Wang; Pau Loke Show; et al. (Frontiers in Nutrition, 2022)
The demand for roasted seaweed sandwich (Porphyra yezoensis) product has risen in recent years. The product slicing process has created a huge number of scraps that are not utilized effectively. Three lactic acid bacteria (LAB) strains were used to ferment P. yezoensis sauces in this study, including Lactobacillus fermentum, Lactobacillus casei, Streptococcus thermophilus, and the mixed strains (1:1:1, v/v). The fermentation characteristics, antioxidant capacity in vitro, sensory properties, and flavoring substances of fermented P. yezoensis sauces were analyzed. After 21 days of fermentation, all LAB strains grew well in the P. yezoensis sauces, with protease activity increased to 6.6, 9.24, 5.06, and 5.5 U/mL, respectively. Also, the flavors of P. yezoensis sauces fermented with L. casei and L. fermentum were satisfactory. On this premise, gas chromatography-mass spectrometry (GC-MS) was used to investigate the changes in gustatory compounds in P. yezoensis sauces fermented with L. casei and L. fermentum. In general, 42 and 41 volatile flavor chemicals were identified after the fermentation of L. casei and L. fermentum. Furthermore, the fermented P. yezoensis sauce possessed greater DPPH scavenging activity and ferric-reducing ability power than the unfermented P. yezoensis. Overall, the flavor and taste of P. yezoensis sauce fermented by L. casei was superior.